2014
DOI: 10.1093/pcp/pcu001
|View full text |Cite
|
Sign up to set email alerts
|

High CO2 Triggers Preferential Root Growth of Arabidopsis thaliana Via Two Distinct Systems Under Low pH and Low N Stresses

Abstract: Biomass allocation between shoots and roots is an important strategy used by plants to optimize growth in various environments. Root to shoot mass ratios typically increase in response to high CO2, a trend particularly evident under abiotic stress. We investigated this preferential root growth (PRG) in Arabidopsis thaliana plants cultivated under low pH/high CO2 or low nitrogen (N)/high CO2 conditions. Previous studies have suggested that changes in plant hormone, carbon (C) and N status may be related to PRG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 74 publications
3
38
0
Order By: Relevance
“…Ammonium uptake takes place by two constitutive ammonium transporters (LATS and HATS) and causes an increase in leaves ammonium content . These two transporters are highly responsive to the ammonium supply and are strongly repressed in the presence of high external ammonium supply as well as high internal glutamine content . Ammonium as a toxic substance downregulates ammonium uptake that could be related to its suppressive effects .…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium uptake takes place by two constitutive ammonium transporters (LATS and HATS) and causes an increase in leaves ammonium content . These two transporters are highly responsive to the ammonium supply and are strongly repressed in the presence of high external ammonium supply as well as high internal glutamine content . Ammonium as a toxic substance downregulates ammonium uptake that could be related to its suppressive effects .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the form of nitrogen can also affect photosynthetic characteristics and the metabolism of different nitrogen forms is different. Most studies have shown that eCO 2 is less conducive for the absorption and transformation of nitrate by plants compared with that of ammonium [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Growth modulation via IAA has also been observed under elevated [CO 2 ] in Arabidopsis (Hachiya et al , 2014) and in tomato seedlings (Wang et al , 2009), and during drought and low temperatures in rice ( Oryza sativa ) (Zhang et al , 2009; Du et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Elevated CO 2 increased carbohydrate and IAA concentrations and promoted growth in Arabidopsis thaliana (Teng et al , 2006; Hachiya et al , 2014) and tomato seedlings ( Solanum lycopersicum ; Wang et al , 2009) but reduced IAA concentrations in roots of sweet pepper ( Capsicum annuum ; Piñero et al , 2014). Niu et al (2011) showed that the auxin-dependent signalling pathway is required for enhancing root development under elevated CO 2 in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%